MENC handbook of research on music learning - Colwell, Richard 1930-; Webster, Peter Richard (Oxford University Press, 2011)
This volume brings together the best and most current research on methods for music learning, focusing squarely on the profession's empirical and conceptual knowledge of how students gain competence in music at various ages and in different contexts. The book takes a broad theoretical perspective on current, critical areas of research, including music development, music listening and reading, motivation and self-regulated learning in music, music perception, and movement.